Ambient noise tomography of Gran Canaria island (Canary Islands) for geothermal exploration. (February 2023) - Cabrera-Pérez, Iván; Soubestre, Jean; D'Auria, Luca; van Dorth, David Martínez; Ledo, Juanjo; Piña-Varas, Perla; Cervigón-Tomico, Germán; Padilla, Germán D.; Barrancos, José; Pérez, Nemesio M.
Abstract: Ambient noise tomography (ANT) has proved to be efficient in resolving crustal structures for different purposes. Despite the numerous studies carried out in Gran Canaria in the past for purposes of geothermal exploration, ANT had never been used before on this island. We applied this technique to understand Gran Canaria island's shallow structure, determining the 3-D S-wave velocity model of the island and focusing on its implications for geothermal exploration. We used data from 30 seismic stations installed between October 2019 and February 2020. Our findings revealed five relevant velocity anomalies helpful in understanding the island's geology and its geothermal potential. In particular, we identified two high-velocity anomalies in the central part of the island aligned with the primary northwest–southeast structural trends of Gran Canaria. We interpret them as evidence of intrusive volcanic bodies emplaced during the early stages of the island's geological history. We also identified three low-velocity zones located in different parts of the island. We maintain that these anomalies could be associated with porous and highly fractured materials produced during the more recent volcanic episodes. In addition, we observed a spatial correlation of anomalies in the electric conductivity identified in previous studies and strong lateral gradients in our S-wave velocity model. We interpret them as evidence of hydrothermal circulation and thermal anomalies in correspondence of lateral contacts between different geological units and/or faults. Highlights: Ambient Noise Tomography applied for geothermal exploration in Gran Canaria island. Imaged velocity anomalies are related to the main geological structures of the island. Correlation between conductive anomalies and strong velocity gradients in our model.